The Chloroplast Land Plant Phylogeny: Analyses Employing Better-Fitting Tree- and Site-Heterogeneous Composition Models - Sousa, Filipe; Civáň, Peter; Foster, Peter G.; Cox, Cymon J. (Frontiers in Plant Science, 2020)
The colonisation of land by descendants of charophyte green algae marked a turning point in Earth history that enabled the development of the diverse terrestrial ecosystems we see today. Early land plants diversified into three gametophyte-dominant lineages, namely the hornworts, liverworts, and mosses, collectively known as bryophytes, and a sporophyte-dominant lineage, the vascular plants, or tracheophytes. In recent decades, the prevailing view of evolutionary relationships among these four lineages has been that the tracheophytes were derived from a bryophyte ancestor. However, recent phylogenetic evidence has suggested that bryophytes are monophyletic, and thus that the first split among land plants gave rise to the lineages that today we recognise as the bryophytes and tracheophytes. We present a phylogenetic analysis of chloroplast protein-coding data that also supports the monophyly of bryophytes. This newly compiled data set consists of 83 chloroplast genes sampled across 30 taxa that include chlorophytes and charophytes, including four members of the Zygnematophyceae, and land plants, that were sampled following a balanced representation of the main bryophyte and tracheophyte lineages. Analyses of non-synonymous site nucleotide data and amino acid translation data result in congruent phylogenetic trees showing the monophyly of bryophytes, with the Zygnematophyceae as the charophyte group most closely related to land plants. Analyses showing that bryophytes and tracheophytes evolved separately from a common terrestrial ancestor have profound implications for the way we understand the evolution of plant life cycles on land and how we interpret the early land plant fossil record.